Insurance Company's Responsibility for Bank Loan Installment Payments in the Event of Debtor's Death (Study of Court Decision Number 613/Pdt.G/2023/PN Smg) - Dinda Rizka Molina Sitorus; Hasim Purba; Dedi Harianto (Talenta Publisher, Universitas Sumatera Utara, 2025)
Credit agreements between banks and debtors are generally supplemented with credit life insurance to minimize the risk of default due to the death of the debtor. In practice, if the debtor dies, the insurance company is obliged to pay the remaining credit to the bank in accordance with the provisions in the policy. However, in Court Decision Number 613/Pdt.G/2023/PN.Smg, a legal problem was found where the insurance company and the bank did not fulfill their obligations to pay life insurance claims to the debtor's heirs. The issues in this study include how the insurance company's responsibility is regulated in relation to the debtor's life insurance claim and how the judge's considerations and decisions relate to the rejection of claim payments. The research method used in this study is normative, descriptive legal research with a legislative approach and a case study of court decisions, using secondary data with primary and secondary legal materials. The data collection method was conducted through literature study and deductive conclusions were drawn. The results of the study show that the regulation of the insurance company's responsibility in paying debtor life insurance claims as collateral for bank loan repayment is based on Article 246 of the Commercial Code concerning risk transfer agreements with premium payments, as well as Articles 1320 and 1338 of the Civil Code concerning the valid terms of an agreement and the obligation to implement it in good faith. Based on Court Decision Number 613/Pdt.G/2023/PN.Smg, unilateral termination of insurance cooperation without notification to the debtor violates Article 1338 Paragraphs (1) and (3) of the Civil Code. The judge ruled that the rejection of claims was contrary to the legal basis, so that the insurance company was still obliged to pay off the debtor's remaining credit to the bank. Thus, this decision reinforces the principle of pacta sunt servanda (agreements must be fulfilled) and provides legal certainty for debtors and heirs in legal relationships related to credit life insurance.